2012
DOI: 10.3109/00365548.2011.649490
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin 10 and interferon gamma gene polymorphisms with enterovirus 71 encephalitis in patients with hand, foot and mouth disease

Abstract: Enterovirus 71 (EV71) is one of the common causative agents of hand, foot and mouth disease (HFMD), and is associated with several outbreaks with neurological complications including encephalitis. This study investigated the polymorphisms of interferon gamma (IFN-γ)+874 T/A and interleukin 10 (IL-10)-1082 G/A in 65 Chinese patients with EV71 encephalitis and 113 Chinese HFMD patients without complications. The polymorphisms of IFN-γ+874 T/A and IL-10-1082 G/A were determined by polymerase chain reaction (PCR)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Compared to mice with IFNAR deficiency alone, mice with both IFNAR and IFN-␥ receptor (IFN-␥R) deficiency display increased susceptibility to EV71 infection (37), indicating a protective role for IFN-␥. In contrast, expression and gene polymorphism of IFN-␥ have been shown to associate with EV71-induced pulmonary edema and encephalitis in patients (18,38), and exogenous administration of three cytokines (IL-6, IL-13, and IFN-␥) together exacerbates EV71-induced pulmonary abnormality with edema in mice (39). Infection by EV71 may alter IFN-␥ responses, leading to escape from both antiviral strategies and immunopathogenesis.…”
mentioning
confidence: 99%
“…Compared to mice with IFNAR deficiency alone, mice with both IFNAR and IFN-␥ receptor (IFN-␥R) deficiency display increased susceptibility to EV71 infection (37), indicating a protective role for IFN-␥. In contrast, expression and gene polymorphism of IFN-␥ have been shown to associate with EV71-induced pulmonary edema and encephalitis in patients (18,38), and exogenous administration of three cytokines (IL-6, IL-13, and IFN-␥) together exacerbates EV71-induced pulmonary abnormality with edema in mice (39). Infection by EV71 may alter IFN-␥ responses, leading to escape from both antiviral strategies and immunopathogenesis.…”
mentioning
confidence: 99%
“…To our knowledge, only three genetic association studies have addressed susceptibility genes that related to EV71 infection (Chang et al 2008;Yang et al 2001Yang et al , 2012. Some of the results, however, could not be replicated in subsequent studies in other populations.…”
Section: Discussionmentioning
confidence: 96%
“…Individual susceptibility to EV71 infection seems to be variable (Chang et al 2008;Yang et al 2001Yang et al , 2012. Patients with EV71 infection displayed wide clinical spectrum, ranging from asymptomatic or mild hand-foot-mouth disease (HFMD) to severe neurological disease.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many association studies between host genetic factors and EV71 infection have been performed. Our lab has previously demonstrated that polymorphisms in genes of IL-8, IL-10, IFN-γ, IL-6, IL-4, CXCL-10, CCL-2, TLR3, OAS3 and CPTII were associated with the susceptibility and/ or the severity of EV71 infection [24][25][26][27][28][29][30][31][32]. These cytokines/ chemokines and receptors are all necessary for an efficient inflammatory response.…”
Section: Introductionmentioning
confidence: 99%